2005
DOI: 10.1007/bf03215258
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic gold recovery from spent cyanide plating bath solutions

Abstract: Gold-cyanide compounds represent the gold-containing chemicals most widely used in mining and electroplating industries. Despite many efforts focused on the substitution of cyanide salts by less toxic compounds, no successful alternatives have been found. The unique complexing capabilities of cyanide ions in aqueous solutions make these compounds the best choice for the heap leaching process in the gold mining sites or for gold plating applications (1).Wastewater effluents of these processes show significant c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
46
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(48 citation statements)
references
References 21 publications
(24 reference statements)
0
46
0
Order By: Relevance
“…[29][30][31] Photocatalysis has been shown to be an attractive alternative, and using TiO 2 particles in suspension has achieved promising results. [32][33][34] The metal ions present in effluents are usually found complexed by substances such as EDTA or Cyanide, species widely used in industrial applications.…”
Section: Photo-assisted Electrolytic Copper Ions Removalmentioning
confidence: 99%
See 2 more Smart Citations
“…[29][30][31] Photocatalysis has been shown to be an attractive alternative, and using TiO 2 particles in suspension has achieved promising results. [32][33][34] The metal ions present in effluents are usually found complexed by substances such as EDTA or Cyanide, species widely used in industrial applications.…”
Section: Photo-assisted Electrolytic Copper Ions Removalmentioning
confidence: 99%
“…Normally, in order to add a hole scavenger (generally an alcohol), it is necessary to enhance the reduction of the metal complex, thereby inhibiting the oxidation of CN -, resulting in an undesirable accumulation of toxic species in the solution. 29 Although the results obtained with particulate materials have shown that the heterogeneous photocatalysis is a promising alternative of remediation for this type of effluent, findings have also revealed disadvantages related with the separation, recovery and recycling of the catalyst and metallic deposits from the treated effluents. [29][30][31][32][33][34] An alternative and effective methodology to overcome these inconveniences is photoassisted electrolysis.…”
Section: Photo-assisted Electrolytic Copper Ions Removalmentioning
confidence: 99%
See 1 more Smart Citation
“…Specially, the metal ions removal has received certain attention due to the feasibility of valuable metals recuperation 7,9,12 . The metal ions present in effluents are usually found to be complexed by substances like EDTA or Cyanide, species widely employed for industrial applications.…”
mentioning
confidence: 99%
“…For example, whereas the EDTA oxidation is achieved, the metal ions reduction is not attained 9 . On the other hand, when cyanide complexes are present, normally it is required to add a hole scavenger (generally an alcohol) to enhance the metal complex reduction, inhibiting the oxidation of CN -, resulting in an undesirable accumulation of such toxic species in the solution 7 . Although the results obtained with particulate materials have shown that the heterogeneous photo-catalysis is a promising alternative for remediation of that type of effluents, they have also revealed disadvantages related with the separation, recovery and recycling of the catalyst and metallic deposits from the treated effluents 4,5,14 .…”
mentioning
confidence: 99%